The free economy, the welfare state and government borrowing - Philip Booth (Institute of Economic Affairs (IEA), 2010)
Modern welfare states undermine human flourishingIn the thirty-first IEA Discussion Paper, Professor Philip Booth explains how modern welfare states and high levels of public debt undermine human flourishing. His arguments are presented in the context of Catholic social teaching.Professor Booth asks whether, in the field of welfare, the state is serving the family - as should be the case - or the other way round. Are our systems of welfare, supporting the networks of solidarity, reciprocity and community or displacing them? Are our systems of welfare supporting human flourishing through family formation, work and saving or discouraging these things? Are our systems of welfare imposing upon people who have not yet been born obligations that we do not know that they will be able to meet?A time of financial stringency is a good time to ask these questions because, if savings are to be made, it is much better that welfare is reformed at the same time in ways that better enable human flourishing.
Keywords: 330; Economic liberalism; Market economy; Welfare state; Public debt; Wirtschaftsliberalismus; Marktwirtschaft; Sozialstaat; Öffentliche Schulden